Iyo si Malik - Bayot, Cassey; Ramos, Saturnino Jr.; Suarez, Xeph ([Place of production not identified] Hombrella Pictures, 2014)
"Toto, 8, and JR, 10, are victims of a recent armed conflict in their city. While playing among the war ruins, they discuss and re-enact their individual war experiences. This story is set in Zamboanga City after the standoff in 2013 between the forces of the Republic of the Philippines and a faction of the Moro National Liberation Front led by Habier Malik.:--Xeph Suarez.
Summary taken from: https://www.imdb.com/title/tt12155070/plotsummary?ref_=tt_ov_pl
Story by Xeph Suarez.
Cassey Bayot, Saturnino Ramos Jr.
DVD.
In Filipino and Subanen language.
Keywords: Drama; Short film